Prognostic Model of Microbial Resistance Based on the Relationship between Antibiotic Resistance and Consumption - Arepeva M.A.; Kolbin A.S.; Sidorenko S.V.; Kurylyov A.A.; Balykina Yu.E.; Mukhina N.V.; Spiridonova A.A. (Клиническая микробиология и антимикробная химиотерапия, 2016)
Acquired bacterial resistance is one of the leading causes of morbidity and mortality attributed to infectious diseases. Simulations may provide opportunity to predict further spread of resistance and, to some extent, manage it. The objective of this study was to construct a model describing relationship between microbial resistance and antibiotic consumption. At the first step, an analysis of the published models developed to achieve this goal was performed. At the second step, a cross-sectional, retrospective study was designed and performed to collect clinical and microbiological data for constructing this model. At the third step, the model was constructed and validated. A consumption of different antibiotic classes was shown to have a significant effect on resistance rate. The model may help in predicting antimicrobial resistance trends as well as demonstrates the effect of antibiotic consumption on resistance rates.